Consulting report - transportadora de gas del Perú delivering natural gas to Ayacucho - Vilcahuaman Poma, Katya Rocio (Pontificia Universidad Católica del Perú, 2018)
The purpose of this consultation report was to examine the opportunities available to TgP for achieving its overarching strategic objectives, particularly its aims of bolstering corporate reputation and creating shared value for the communities which are impacted by the firm’s operations. The scope of this examination was confined primarily to opportunities in the Huamanga province, due to the fact that there is pre-existing infrastructure there which is currently underutilized. To identify the best opportunity available in the area, analyses are conducted on the external, industry, and internal levels for TgP. From this, the opportunity for TgP to transport natural gas to the Huamanga region was identified. To determine the best method by which to execute on this opportunity, the existing literature was reviewed and complemented with quantitative and qualitative analysis. The chosen method is to transport natural gas to Huamanga via a polyethylene pipeline approximately 6.3 Km long and 8 inches in diameter. While the implications and projected revenues of this proposal are rather minimal in the scale of TgP’s overall operations, the project is likely to constitute a community outreach victory regarding Huamanga. In short, this is a triumph for all parties involved, as the community benefits from access to natural gas, while TgP benefits from making use of idle infrastructure and capabilities, and the government benefits from the furthering of their Massification initiative. The results and specific recommendations of this report are not generalizable, as the solution is purpose-built for the area. However, this may also serve as a pilot proposal for similar socially-driven ventures in other regional communities if executed successfully.

El propósito de este informe de consultoría fue el de examinar las oportunidades disponibles para que TgP logre sus objetivos estratégicos, particularmente sus objetivos de reforzar la reputación corporativa y crear valor compartido para las comunidades que colindan con las operaciones de la empresa. El alcance de este estudio se limitó principalmente a las oportunidades en la provincia de Huamanga, debido a la presencia una infraestructura preexistente que en la actualidad esta no es utilizada. Para identificar la mejor oportunidad disponible, los análisis se realizaron a nivel externo, industrial e interno de TgP. A partir de esto, se identificó la oportunidad para TgP de transportar gas natural a la región de Huamanga. Para determinar el mejor método disponible para la ejecución de dicha oportunidad, la literatura existente fue revisada y complementada con los análisis cuantitativo y cualitativo. El método elegido es el de transportar gas natural a Huamanga a través de una tubería de polietileno de aproximadamente 6.3 km de largo y 8 pulgadas de diámetro. Si bien las implicaciones y los ingresos proyectados de esta propuesta son bastante mínimos en la escala de las operaciones generales de TgP, es probable que el proyecto constituya una victoria de alcance comunitario con respecto a Huamanga. En resumen, se trata de un triunfo para todas las partes involucradas, ya que la comunidad se beneficia del acceso al gas natural, mientras que TgP se beneficia de la infraestructura inutilizada y el gobierno se beneficia de la promoción de su iniciativa de Masificación de energía. Los resultados y las recomendaciones específicas de este informe no son generalizables, ya que la solución está especialmente diseñada para la región. Sin embargo, esto también puede servir como una propuesta piloto para iniciativas sociales similares impulsadas en otras comunidades regionales si se ejecuta con éxito.
Keywords: Gas natural--Perú--Ayacucho; https://purl.org/pe-repo/ocde/ford#5.02.04